Math

posted by .

5(-3x - 2) - (x - 3) = -4(4x + 5) + 13

Answer
Multiply factors.
-15x - 10 - x + 3 = -16x - 20 +13

Group like terms.
-16x - 7 = -16x - 7

Add 16x + 7 to both sides and write the equation as follows

0 = 0

  • Math -

    Looks good.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Intermediate Algebra

    Am I going in the right track? 8x -1/x + 5x - 3/2x = 16x^2 - 2x/2x^2 + 5x^2 - 3x/2x^2 16x^2 - 2x + 5x^2 - 3x/2x^2 =21x^2 - 5/2x^2 Find the LCD 6/7z- 28, 8/x^2 -4x = 7x(x-4) Simplify 3x^2 - 2x/15x-10 = x/5 Let's start by looking at
  2. algebra

    Solve the system by addition or substitution. 16x-4y=20 y=4x-4 I ask for help with this and forgot to add the problem. can anyone help me understand how to do this?
  3. Algebra

    There are two solutions to | 16x - 5 | = 3. The greatest solution is ___. Since the expression, 16x - 5, can be either positive or negative, solve for both. 16x - 5 = 3 16x = 8 x = .5 -(16x - 5) = 3 -16x + 5 = 3 -16x = -2 x = 1/8 You …
  4. algebra

    x^2 +16x+64 x^2+16x=64 (x=3)^2=16x-64 16x=-64 x=-4 Check this problem please
  5. math

    The question is (2x+1)^2-2(2x^2-1) in simplest form Is this correct?
  6. Pre-Calculus

    Help please If f(x)=8x and g(x)=2x+1 find (fog)(x) 16x^2+8x 16x+1 16x+8 10x+1
  7. math - please help

    Find the HCF and LCM of: 1 + 4x + 4x^2 - 16x^4.. ,1 + 2x - 8x^3 - 16x^4.., 16x^4 + 4x^2 + 1
  8. Math

    Which of the following expressions is equivalent to (-2x^5 y^2)^4 A. -16x^20 y^8 B. -8x^10 y^8 C. -8x^9 y^6 D. 16x^9 y^6 E. 16x^20 y^8
  9. Math

    I sent this in a little while back but the file got corrupted and I have to re do it and I forgot the answer please if it is not done today I fail the year. Simplify the polynomial 16x^2 + 2 + 2x - 15x^2 - 1 + 14x A:31x^2 + 16x + 1*** …
  10. Math

    1. 16x^2 + 2 + 2x - 15x^2 - 1 + 14x a. 31x^2 + 16x + 1 b. x^2 - 12x + 1 c. x^2 + 16x + 1* d. x^2 + 16x + 2 2. 3x^2 + 6 - 2x + 5x - 4^2 + 9 a. -x^2 + 3x + 15* b. 7x^2 + 3x + 3 c. x^2 - 3x + 15 d. -x^2 + 7x + 15 3. 2x^2 + 6x - 7x + 8 …

More Similar Questions